Volume 3A: Heat Transfer 2013
DOI: 10.1115/gt2013-95423
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of a U-Bend for Minimal Pressure Loss and Maximal Heat Transfer Performance in Internal Cooling Channels

Abstract: A multi-objective design optimization is performed on a U-bend in serpentine internal cooling channels. The aim is to achieve both minimized total pressure loss and maximized heat transfer ability. The optimization technique used is a two-level routine developed at the Von Karman Institute for Fluid Dynamics (VKI), featuring a Differential Evolution algorithm assisted by a metamodel, which is continuously updated during the course of the optimization process to increase its accuracy The geometries are carefull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…When increasing w 2 to 0.98 (Opt0), we obtain a 40.3% increase in N u. Again, we obtain much more N u increase, compared with the value (16.9%) reported by Verstraete et al [4]. However, this design is not favorable, since it generates excessive flow separation.…”
Section: Function or Variablecontrasting
confidence: 41%
See 1 more Smart Citation
“…When increasing w 2 to 0.98 (Opt0), we obtain a 40.3% increase in N u. Again, we obtain much more N u increase, compared with the value (16.9%) reported by Verstraete et al [4]. However, this design is not favorable, since it generates excessive flow separation.…”
Section: Function or Variablecontrasting
confidence: 41%
“…There are two main classes of design optimization methods: gradient-free and gradient-based methods. A number of researchers have optimized turbine internal cooling designs using the gradient-free methods such as artificial neural network, genetic algorithms, and design of experiments [3][4][5][6]. However, one of the issues with these gradient-free methods is that their computational cost scales exponentially with the number of design variables [7].…”
Section: Introductionmentioning
confidence: 99%
“…Verstraete and Li [11] followed another approach to reach the goal, getting optimum design for U-bend, using geometry parameterization using several 3D simulations. Their results showed that U-bend shape could change to minimize the pressure drop (69.2% of original) or maximize the heat transfer rate (116.93% of original).…”
Section: /15mentioning
confidence: 99%
“…Authors were able to simultaneously reduce flow velocity variance and pressure drop by 36% and 26%, respectively. The optimization of Ubend duct was performed by Verstraete et al (2013) with use of metamodel assisted Differential Evolution algorithm 16 in order to minimize the total pressure drop. 16 Authors compared two surrogates: based on Kriging and based on ANN to assess their performance.…”
Section: Introductionmentioning
confidence: 99%